Content Analysis of Islamic Religious News on the Radar Kudus Website - Achdariyaturrohma, Octa Afriana; Rohimi, Primi (Universitas Muhammadiyah Yogyakarta, 2026)
The development of digital technology has fundamentally changed the way people obtain and interpret religious information. Online media no longer merely serve as a means of conveying information but has also become a crucial space for the formation of religious discourse and identity. Within this framework, Radar Kudus occupies a strategic position as a local media outlet present in a community with a strong Islamic tradition. This study aims to examine how Islam is represented in Radar Kudus's reporting and to encourage the development of religious discourse in the digital realm. The analysis focuses on Islamic themes, values, and messages constructed through news, particularly in the context of strengthening religious moderation. This study used a qualitative approach and the Krippendorff content analysis method to analyze six Islamic-themed articles published between August and September 2025. The results showed that Radar Kudus consistently presented a moderate, educational, and contextual representation of Islam, emphasizing Sufi values, ethics, and local culture, such as tolerance, thus functioning not only as an information medium but also as a means of da'wah responsive to social dynamics.